POTENCIAL LARVICIDA DO FRUTO DE Caryocar brasiliense Cambess. EM Aedes aegypti, E EFEITOS TÓXICOS IN VITRO E IN VIVO - Raquel da Silva Vieira (2024)
The increasing resistance of Aedes aegypti to conventional chemical insecticides and arbovirus epidemics leads to a need to find sustainable alternatives to control the vector, especially in tropical and subtropical countries. Brazil has a plant biodiversity in the Cerrado biome that offers a vast potential of bioactives, highlighting the importance of studies to explore these natural substances. The Caryocar brasiliense Cambess stands out, a native fruit known as pequi, rich in bioactive substances in its chemical composition, so the objective of this study is to evaluate the larvicidal potential of the fruit of Caryocar brasiliense Cambess. in Aedes aegypti and toxic effects in vitro and in vivo. The extracts of pequi pulp and almond were obtained by maceration in ethanol solvent, filtered and routeevaporated. In the chemical analysis, the samples were submitted to the fatty acid esterification reaction, injected in a gas chromatograph coupled to Mass Spectrometry (GC/MS) and four fatty esters were identified in the pulp extract and five in the almond extract, the majority being palmitic and oleic derivatives. The samples were tested in third instar larvae of Aedes aegypti of the Rockefeller strain and obtained larvicidal activity at all tested concentrations of 0.3 to 1.0 mg/mL, with the almond extract having the best effect on mortality, with LC50 0.58 and LC90 1.15 mg/mL, in relation to the pulp LC50 0.64 and LC90 1.69 mg/mL. The morphological analysis showed changes in the color of the larvae exposed to the treatment, such as loss of continuity of the digestive tract, partial loss of the peritrophic matrix and alteration in the anal lobe. In the in vitro tests, two cell lines were tested, one of murine fibroblasts 3T3 (ATCC CRL-1658) and the other of human umbilical cord HUVEC (ATCC CRL-1730), obtaining a parameter of inhibition of 50% of cell growth in GI50. The ethanolic extracts of the pequi pulp and almond did not present cytotoxicity at the maximum concentration tested, GI50 >250 μg/ml, compared to doxorubicin which presented cytotoxicity at 0.25 and 0.023 μg/ml, showing toxicity 1000 times lower in the 3T3 strain (ATCC CRL-1658) and 10,000 times lower in the HUVEC strain (ATCC CRL-1730) when compared to the same chemotherapy drug. The in vivo tests were carried out in male mice of the BALB/c strain in four groups with three animals each, which received the extracts of the pulp and almond diluted in olive oil at doses 2000 mg/kg (G1), 300 mg/kg (G2), 50 mg/kg (G3) and 5 mg/kg (G4) and a control (G5) that received only olive oil. All in a single dose (200 μL) via gavage after 8 hours of fasting and observed for a period of 30 minutes, 1, 2, 4, 6, 12 and 24 hours, and daily for 17 days. After the administration of the doses, a Hippocratic screening was performed to evaluate the parameters of anesthesia, general activity, grasping force, response to touch, tremors, locomotion, vocal thrill, irritability, contortion, ptosis, lacrimation, respiration, ataxia, feeding with water and feeding with food, and normal values were found in the parameters observed, with no signs of toxicity, and no death in the different concentrations tested. obtaining an estimated LD50 greater than 2000 mg/kg. Liver and kidneys of the animals tested with the pulp extract were collected for histopathological parameters, steatosis (fatty degeneration), necrosis, leukocyte infiltrate, hyaline degeneration, hydropic degeneration and fibrosis, showed histological patterns within the normal range. Therefore, the ethanolic extracts of the pulp and almond of Caryocar brasiliense have been shown to be active against Aedes aegypti larvae, with toxic safety in vitro and in vivo.